Uji Efektivitas Serbuk Tanaman Tapak Dara (Catharanthus roseus L.) Terhadap Serangan Nematoda Puru Akar Meloidogyne spp. pada Tomat (Lycopersicum esculentum Mill.) - Tiki Andriani; Edwin Noor Fikri; Ismed Setya Budi (JURNAL PROTEKSI TANAMAN TROPIKA, 2018)
The purpose of this research was to know the most effective dose of periwinkle plant (Catharanthus roseus L.) as botanical nematicide in suppressing the attack of root knot nematode caused by Meloidogyne spp. on tomato root. Treatment tested were K: control (without periwinkle plant powder), S1: periwinkle plant powder 30 g / polybag, S2: periwinkle plant powder 40 g / polybag, S3: periwinkle plant powder 50 g / polybag and S4: periwinkle plant powder 60 g / polybag. The results showed that periwinkle nematicide significantly effected the disease intensity of Meloidogyne spp. on the tomato root with 60 gram of periwinkle powder or as of 12.5% showing the lowest intensity even the wet weight measurement and nematode population showed no significant effect.